Fruit softening: revisiting the role of pectin - Wang, Duoduo; Yeats, Trevor H.; Uluisik, Selman; Rose, Jocelyn K.C.; Seymour, Graham B. (Elsevier, 2018)
Fruit softening is a major determinant of shelf life and commercial value. Here, we highlight recent work that revisits the role of pectin in fruit softening and primary cell wall structure. These studies demonstrate the importance of pectin and the link between its degradation and softening in fleshy fruits.